Hubungan Intensitas Penggunaan Make Up Terhadap Tingkat Kepercayaan Diri Mahasiswi Fakultas Psikologi Universitas Prima Indonesia - Swita Swita; Angelica Cecilia; Stephanie Stephanie; Shandya Silviyani; Achmad Irvan Dwi Putra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Self-confidence is an important aspect of female student self-development, especially in supporting active participation in academic and social activities. However, insecurity due to dissatisfaction with physical appearance is still a common phenomenon among female students. One of the strategies used to overcome this is the use of makeup. This study aims to determine the relationship between the intensity of makeup use and the level of confidence in female students of the Faculty of Psychology, Universitas Prima Indonesia. This study uses a quantitative approach with a correlational method. A sample of 190 female students was selected through purposive sampling techniques. The data collection instrument used the Likert scale, with the makeup intensity aspect referring to Ajzen's theory (frequency and duration), and the confidence aspect referring to Lauster's theory. The results of the Pearson Product-Moment analysis showed a significant negative correlation (r = -0.479; p < 0.05), which indicates that the higher the intensity of makeup use, the lower the confidence level. These findings suggest that makeup is often used as compensation for insecurity, rather than as an authentic indicator of self-confidence.